E-Commerce In Purchase Decision: A Systematic Literature Review - Musnaini; Masriani, Ida; Hasbullah, Husni; Tialonawarmi, Feny; Hendriyaldi; Asrini (Jurnal Mebis, 2025)
This study reviews the connection between e-commerce and its influence on purchase decisions on e-commerce platforms through a Systematic Literature Review (SLR) method. The main factors that have been proven to significantly influence purchase decisions include product quality, product ratings and reviews, price, information quality, trust, security, service quality, perceived risk, and purchase intention. These findings indicate that a deep understanding of these variables can help business actors and marketers develop more effective strategies to increase purchase conversions in the e-commerce domain. Furthermore, this study also identifies opportunities for further research related to the integration of e-commerce systems and the development of marketing strategies based on consumer behavior data. This SLR seeks to encourage future research and practical applications within e-commerce.